Insight into the dynamics of fluid conveying tiny particles over a rotating surface subject to Cattaneo–Christov heat transfer, Coriolis force, and Arrhenius activation energy - Ali, Bagh (2022)
This article addressees the dynamics of fluid conveying tinny particles and Coriolis force effects on transient rotational flow toward a continuously stretching sheet. Tiny particles are considered due to their unusual characteristics like extraordinary thermal conductivity, which are significant in advanced nanotechnology, heat exchangers, material sciences, and electronics. The main objective of this comprehensive study is the enhancement of heat transportation. The governing equations in three dimensional form are transmuted in to dimensionless two-dimensional form with implementation of suitable scaling transformations. The variational finite element procedure is harnessed and coded in Matlab script to obtain numerical solution of the coupled non-linear partial differential problem. It is observed that higher inputs of the parameters for magnetic force and rotational fluid cause to slow the primary as well as secondary velocities, but the thermophoresis and Brownian motion raise the temperature. However, thermal relaxation parameter reduces the nanofluid temperature. The velocities for viscosity constant case are faster than that for the variable viscosity, but temperature and species concentration depict opposite behavior.